Analyzing Dual-Task Paradigms to Improve Postconcussion Assessment and Management. - Robertson, Diana; Lempke, Landon B.; Lynall, Robert C. (Journal of Sport Rehabilitation, 2024)
Context: Dual-task (simultaneous cognitive–motor activities) assessments have been adapted into reliable and valid clinical concussion measures. However, abundant motor and cognitive variations leave researchers and clinicians uncertain about which combinations elicit the intended dual-task effect. Our objective was to examine differences between commonly employed dual-task motor and cognitive combinations among healthy, college-aged individuals. Design: Cross-sectional laboratory study. Methods: Twenty participants (age: 21.3 [2.4] y; height: 176.0 [9.1] cm; mass: 76.0 [16.4] kg; 20% with concussion history) completed 4 motor tasks (gait, tandem gait, single-leg balance, and tandem balance) under 5 cognitive conditions (single task, subtraction, month reversal, spelling backward, and visual Stroop) in a research laboratory. The motor performance outcomes were spatiotemporal variables for gait and tandem gait and center of pressure path length (in centimeters) for single-leg and tandem balance. Cognitive outcomes were response rate (responses/second) and cognitive accuracy. We used separate repeated-measures analyses of variance for each motor and cognitive outcome with post hoc Tukey t tests. Results: Gait velocity, gait stride length, and tandem gait velocity demonstrated significant cognitive–motor interactions (P's <.001) such that all dual-task conditions resulted in varyingly slower or shorter movement than single task. Conversely, single-leg balance (P =.627) and tandem balance (P =.434) center of pressure path length did not significantly differ among the dual-task cognitive conditions or relative to single task. Statistically significant cognitive–motor interactions were observed only for spelling backward accuracy (P =.004) and response rates for spelling backward, month reversal, and visual Stroop (P's <.001) such that worse accuracy, but faster response rates, occurred during motor tasks. Conclusions: Gait and tandem gait motor tasks accompanied with spelling backward or subtraction cognitive tasks demonstrated consistently strong dual-task effects and, therefore, may be the best suited for clinical and research use following concussion.